Error analysis on auxiliary verbs do/ does, have/ has, and had - Veni Nella Syahputri; Meta Keumala; Zahratul Idami (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2022)
Error analysis is considered as a significant part in second and foreign language teaching. It helps teachers in understanding the better approaches for instructing by giving the input on the errors produced by students because students can learn from their errors. This study aimed at analyzing the errors produced by students in using do/does, have/has, and had. The methodology employed in this study was qualitative design. The population in this study was 149 students from all study programs. During the data collection, random sampling was utilized and there were 19 female students and 19 male students involved as the sample of this study. The instrument of this study was the instrument of this research adapted from Harald (2011). Later, the data were analyzed using Taxonomic Analysis. The result of the test showed that from the 38 students as the sample, 12 students were in high level of error, 8 students were in the level of fair, and 18 students were considered in the low level of error. These errors are assumed due to the interference of students’ first language structure to English.  DOI: 10.26905/enjourme.v7i1.6684